The marriage plot [compact disc, unabridged] - Eugenides, Jeffrey (Macmillan Audio, 2011)
Madeleine Hanna was the dutiful English major who didn't get the memo. While everyone else in the early 1980s was reading Derrida, she was happily absorbed with Jane Austen and George Eliot. But now, in the spring of her senior year, Madeleine has enrolled in a semiotics course to see what all the fuss is about, and, for reasons that have nothing to do with school, life and literature will never be the same.